Assessment of eHealth literacy among cardiovascular disease patients and analysis of influencing factors - Wang, Wei; Jiao, Mengfan; Zhao, Xiaojing; Chen, Chunxu; Jiang, Wenhui; Zhang, Xiaoman (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to comprehensively evaluate the eHealth literacy of patients with cardiovascular diseases and uncover the associated influencing factors. The findings are intended to lay a solid foundation for formulating targeted strategies to enhance the health literacy of this patient population.MethodsBetween October 2023 and June 2024, a purposive sampling approach was employed to recruit patients with cardiovascular diseases visiting the cardiology department of a tertiary hospital in Shandong Province. The eHealth Literacy Scale (eHEALS) was utilized to assess the eHealth literacy levels of the participants. Based on the assessment results, the subjects were classified into qualified and unqualified groups. Subsequently, logistic regression analysis was conducted to identify the influencing factors underlying eHealth literacy.ResultsThe eHealth literacy score among cardiovascular disease patients was 20.46 ± 9.54, with a passing rate of 38.6%. The overall mean score across all items was 2.5 ± 1.19. Specifically, for the sub-domains of internet health information service capabilities and application abilities, evaluation capabilities of internet health information and services, and decision - making capabilities of internet health information and services, the mean scores were 2.49 ± 1.18, 2.67 ± 1.32, and 2.66 ± 1.35, respectively. Findings from binary logistic regression analysis suggest that education level, sleep quality, residing in close proximity to a medical institution (distance < 5 km), prior utilization of medical information websites or search engines, as well as the interaction between proactive health awareness and utilization of medical information websites or search engines, were all influencing factors for the qualification of e - health literacy (p < 0.05). These results underscore the complex interplay of multiple factors in determining patients’ eHealth literacy levels, which has important implications for the design and implementation of effective health information dissemination and patient education strategies in the digital age.ConclusionOur findings reveal that the eHealth literacy among cardiovascular disease (CVD) patients remains at a relatively low level. This situation underscores the urgent need for interventions aimed at enhancing patients’ proactive health awareness and delivering targeted eHealth training programs. Specifically, such initiatives should be designed to enable patients to accurately access, comprehensively understand, critically evaluate, and effectively apply health information in the digital realm. By doing so, we can empower CVD patients to better manage their health in the context of the digital age, ultimately leading to an improvement in their eHealth literacy levels. These efforts are not only crucial for individual patient care but also have broader implications for optimizing health outcomes at a population level.